Long-Term Posttraumatic Growth in Victims of Terrorism in Spain - Fausor, Rocío; Sanz, Jesús; Navarro-McCarthy, Ashley; Gesteira, Clara; Morán, Noelia; Cobos-Redondo, Beatriz; Altungy, Pedro; Marqueses, José M. S.; Sanz-García, Ana; García-Vera, María P. (Frontiers in Psychology, 2022)
Background: Scientific literature on posttraumatic growth (PTG) after terrorist attacks has primarily focused on persons who had not been directly exposed to terrorist attacks or persons who had been directly exposed to them, but who were assessed few months or years after the attacks. Methods: We examined long-term PTG in 210 adults directly exposed to terrorist attacks in Spain a mean of 29.6 years after the attacks (range: 2-47 years). The participants had been injured by a terrorist attack (38.6%) or were first-degree relatives of people who had been killed or injured by a terrorist attack (41.4% and 20%, respectively). They completed diagnostic measures of emotional disorder and measures of PTSD and depression symptomatology, optimism, and PTG. Results: Multiple regression analyses revealed gender differences (women reported higher levels of PTG than did men) and a positive linear relationship between PTG and cumulative trauma after the terrorist attack. Some PTG dimensions were significantly associated with PTSD symptomatology, these associations being linear, not curvilinear. However, PTG was not associated with depression symptomatology, diagnosis of emotional disorders, age, elapsed time since the attack, or optimism. In comparison with survivors assessed 18 years after the 1995 Oklahoma City bombing, Spanish victims of terrorism showed higher levels of appreciation of life, but lower levels of relating to others and spiritual change. Conclusion: The findings underscore the influence of gender on PTG and provide support to the hypothesis that some emotional distress may be a necessary condition of PTG. Future studies on PTG after terrorist attacks should take into consideration the characteristics of the terrorist attack itself and the contexts of violence and threat in which it occurred. The political, social, and cultural characteristics of the community affected by it and the profile and characteristics of other traumatic events suffered after the attack should also be taken into account in further research.